Signaling worker quality in a developing country: Lessons from a certification program - M. Antonella Mancino; Leonardo Fabio Morales; Diego F. Salazar (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We evaluate the returns to signaling occupation-specific skills using unique administrative data from a nationwide certification program in Colombia. The program certifies skills and issues three certificates: basic, intermediate, and advanced. We use regression discontinuity methods to compare workers' earnings around certificateassignment thresholds. Signaling advanced occupation-specific skills yields significant returns: 9.7%, on average, within two years of certification. Instead, we find no effects from signaling basic or intermediate occupation-specific skills. Our analysis reveals that the primary mechanism behind the observed income effects associated with the advanced certificate is the ability to signal occupation-specific skills to potential employers.
Keywords: J01; J31; J44; 330